PENGATURAN KOORDINASI PENGENDALIAN KEAMANAN ANTARA KANTOR PUSAT DIREKTORAT KEAMANAN PENERBANGAN DAN KANTOR OTORITAS BANDAR UDARA (Studi di Kantor Otoritas Bandar Udara Wilayah VI Padang) - Adrian, Dani (Universitas Ekasakti, 2018)
Fulfillment of rules against a high standard of aviation security is an absolute necessity in the aviation world. The arrangement of the coordination of aviation security control between the Head Office of the Directorate of Aviation Security and the Office of the Airport Authority is essential to protect the safety, regularity, and efficiency of civil aviation activities in its territory. The implementation of the flight security control coordination arrangement between the Head Office of the Directorate of Aviation Security and the Office of the Airport Authority has a problem namely the Directorate of Aviation Security still performs the functions of the controlling activities, the authority of signing the extension of licensing to the Head of the Office of the Authority Authority has not been implemented, the aviation security inspector's mutation from the Aviation Security Directorate's Head Office has not worked properly, and the fulfillment and distribution of budgetary requirements for the implementation of the control and supervision of the Office of the Airport Authority has not been met.